Book Review: Trail of Story: Traveler's Path (Johnson) - Burbank, Carol (The Trumpeter, 2012)
Leslie Main Johnson’s detailed study of the ethnoecology of Gitksan, Witsuwit’en and Gwich’in indigenous groups of northern Canada explores native people’s intimate and narrative understanding of land, landscape and community. Thoroughly exploring the nuances of indigenous language and “trail of story” about their environs, Johnson does not neglect the nuances of western colonialist language about ecology, mapping and land. Her carefulness results in articulate academic and philosophical conclusions about the often damaging, always challenging adaptations required of native communities today.